Precise fiber alignment in stereolithography (SLA) 3D printing of composite polymers - Kunal Manoj Gide; Clara Elise Tranchemontagne; Muhammad Zaryyab Sardar; Z. Shaghayegh Bagheri (Hybrid Advances)
Additive manufacturing (AM) has advanced significantly, yet challenges remain in producing composites with tailored properties. Stereolithography (SLA), a high-resolution AM technique, struggles to achieve controlled fiber orientation in composite materials. This study addresses this limitation by integrating an in-house electromagnetic filler alignment system into a commercial SLA 3D printer. The system uses electromagnets to align reinforcing fillers at 0° and 90° during printing. Acrylic resin-cobalt powder composites were fabricated and analyzed using optical microscopy, tensile testing, micro-indentation, and scanning electron microscopy (SEM). Microscopy confirmed successful fiber alignment with the electromagnet system. Compared to the control (pure resin) and randomly oriented samples, the aligned composites exhibited lower stiffness but significantly enhanced ductility. Specifically, the strain at failure increased from 1.4 % in the control samples to 7.9 % and 6.8 % in the 0° (perpendicular to loading direction) and 90° (parallel to loading direction) aligned composites, respectively. This marked improvement in strain capacity indicates a clear transition to more ductile behavior, a trend further corroborated by SEM observations. This approach overcomes SLA limitations, enabling controlled filler alignment for enhanced mechanical, thermal, and electrical properties. These advancements hold promise for customized manufacturing in aerospace, automotive, medical, and computing industries.